Algoritma K-Means Clustering Untuk Menentukan Rekomendasi Pemberian Beasiswa Bagi Siswa Berprestasi - Febry Sandrian Sagala; Mugiarso; Wowon Priatna (Journal of Students‘ Research in Computer Science, 2021)
Scholarships are given to underprivileged students or outstanding students through a selection involving certain criteria. The criteria include the average value of report cards, parents' income, distance from home to school, number of dependents of parents, condition of the house, and status of the house. This study aims to assist the selection team in determining the award of scholarships so that they can provide appropriate and inappropriate recommendations, taking into account 6 criteria. The problem is that the existing scholarships are only given to students who do not have a father. The K-Means Clustering Algorithm can help Cluster students who are not eligible and eligible to get scholarship recommendations. The dataset used was 145 instances from the MAS scholarship selection committee. Attaqwa 02 Babylon. The data is calculated and tested using the K-Means Clustering algorithm. The results of the test were 32 people were recommended as eligible and 113 people were not eligible. The K-Means Clustering Algorithm can help the selection team to determine the scholarship award.   Keywords: K-Means Clustering Algorithm, Scholarship Award, Students.   Abstrak   Beasiswa diberikan kepada siswa yang kurang mampu atau siswa berprestasi melalui seleksi yang melibatkan kriteria-kriteria tertentu. Kriterianya antara lain nilai rata-rata rapot, penghasilan orang tua, jarak rumah ke sekolah, jumlah tanggungan orang tua, kondisi rumah, dan status rumah. Penelitian bertujuan untuk membantu tim penyeleksi dalam menetukan pemberian beasiswa sehingga dapat memberikan rekomendasi layak dan tidak layak, dengan pertimbangan 6 kriteria. Masalahnya beasiswa yang ada hanya diberikan kepada siswa yang tidak memiliki Ayah. Dengan Algoritma K-Means Clustering dapat membantu pembuatan Clustering siswa yang tidak layak dan layak untuk mendapatkan rekomendasi beasiswa. Dataset yang digunakan sebanyak 145 instance yang berasal dari panitia seleksi beasiswa MAS. Attaqwa 02 Babelan. Data tersebut dihitung serta pengujiannya menggunakan algoritma K-Means Clustering. Hasil pengujian sebanyak 32 orang direkomendasikan layak dan 113 orang tidak layak. Dengan Algoritma K-Means Clustering dapat membantu tim seleksi untuk menetukan pemberian beasiswa.   Kata Kunci: Algoritma K-Means Clustering, Pemberian Beasiswa, Siswa.